2022
DOI: 10.1111/1541-4337.12918
|View full text |Cite
|
Sign up to set email alerts
|

Iodine from brown algae in human nutrition, with an emphasis on bioaccessibility, bioavailability, chemistry, and effects of processing: A systematic review

Abstract: Brown algae are becoming increasingly popular as a food source and dietary supplement in Europe and other Western countries. As they are highly rich in iodine, they represent a potential new dietary iodine source. Iodine deficiency has been re‐emerging in Europe, and it is important to ensure adequate intake through one's diet. However, macroalgae, and especially brown algae, may contain very high amounts of iodine, and both iodine deficiency and excessive iodine may increase the risk of negative health effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…The great variability in the content of heavy metals and iodine within each species, and several in luencing factors on food quality, are described by several other authors (Banach et al, 2020;Blikra et al, 2022, Steinhagen et al, 2022.…”
Section: Effect Of Growing Conditions On the Content Of Food Hazardsmentioning
confidence: 84%
See 1 more Smart Citation
“…The great variability in the content of heavy metals and iodine within each species, and several in luencing factors on food quality, are described by several other authors (Banach et al, 2020;Blikra et al, 2022, Steinhagen et al, 2022.…”
Section: Effect Of Growing Conditions On the Content Of Food Hazardsmentioning
confidence: 84%
“…A Norwegian report (Duinker et al ., 2020) indicates a bioavailability of 73-78% of iodine from sugar kelp, found in a rat model study. A review article states that the bioavailability of iodine from brown algae is generally high, with in vivo bioavailability ranging from 31 to 90% (Blikra et al, 2022).…”
Section: Bioavailabilitymentioning
confidence: 99%
“…However, iodine bioavailability in different types of seaweed varies, and overall bioavailability estimates are significantly influenced by the iodine status of the study population [ 14 ]. A recent systematic review reported that the bioavailability of iodine from brown algae in vivo varied from 31% to 90% [ 25 ]. The bioavailability of iodine and iodine absorption from different seaweeds has been proposed to be affected by the polysaccharide matrix of the seaweed [ 15 ] and may delay iodine absorption compared with KI.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor affecting bioavailability is the form of iodine in seaweed. Seaweed contains both organic and inorganic iodine [ 26 ], and most brown algae and algae with a high iodine content contain most of the iodine in the form of iodide [ 25 ]. The exact mechanisms underlying the lower iodine bioavailability in sugar kelp compared to KI found in this study were not investigated, but differences in matrix, fibre content, and excretion route could be possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Both insufficient and excessive iodine intake can affect the synthesis of thyroid hormones. Higher iodine consumption (more than the maximum amount of 1100 μg/day; the maximum tolerable value of 600 μg/day set by the Scientific Committee on Food) leads to thyrotoxicosis and autoimmune thyroid problems, while iodine deficiency results in hypothyroidism, goitre, brain damage, and other diseases such as cretinism and stomach cancer [3][4][5][6]. Iodine deficiency disorders (IDDs) affect ca.…”
Section: Introductionmentioning
confidence: 99%